RESILIENCE ATTRIBUTES AMONG UNIVERSITY STUDENTS: A COMPARATIVE STUDY OF PSYCHOLOGICAL DISTRESS, SLEEP DISTURBANCES AND MINDFULNESS - Cher J. McGillivray; Aileen M. Pidgeon (European Scientific Journal, ESJ, 2015)
Australian university students report experiencing higher levels of psychological distress compared to other Australians, and are at increased risk of developing mental health problems. Psychological distress has been connected with poor academic performance, higher attrition rates and sleep disturbances. A protective factor associated with sleep-related selfregulation is mindfulness. Mindfulness based programs have shown benefits in stress reduction and resilience. Resilience is considered a protective factor that interacts with stressors to reduce the likelihood of negative outcomes. Resilience is also associated with positive social and personal well-being together with enhanced mental health and adjustment to university life. The current study examines the attributes of resilient university students, by comparing the differences between high and low resilient students on levels of reported psychological distress, sleep disturbances and mindfulness. A total of 89 university students participated in the study aged between 18 to 57 years. Results showed that university students with high levels of resilience reported significantly lower levels of psychological distress and significantly higher levels of mindfulness, compared to university students reporting low levels of resilience. There were no significant differences reported with regard to sleep disturbances. The findings add to extant knowledge of resilience and provide support for universities to develop strategies that promote resilience in university students to reduce the risk of students developing mental health problems, thus enabling students to flourish under academic pressures.